El efecto de las remesas en el mercado laboral Latinoamérica, período 2000 – 2019. - Zumba Morales, Edinson Omar (2022)
The following research project focuses on analyzing the effect that remittances have on the labor market in Latin America during the period 2000 - 2019; Through macroeconomic variables which are: Remittances% GDP, Under Employment Rate, Foreign Direct Investment and Official Development Aid, an in-depth analysis of the study variables was carried out and different theories of different authors were contrasted with respect to the remittances and the labor market; Regarding the practical study, a VARMA econometric model was used, which when confirming the existence of a stationary series, it was decided to use an Autoregressive Vectors model. The investigation was raised in three different chapters; In chapter I it focuses on contrasting all the relevant theories, definitions and concepts of different authors aimed at researching remittances in the labor market; Chapter II sets out the methodology and type of research used in the project; finally, chapter III expresses the results obtained, the final analysis and discussion of the research.